Tingkat Pengetahuan Berhubungan dengan Sikap Cuci Tangan Bersih Pakai Sabun Sebelum dan Setelah Makan pada Siswa SDN Ngebel Tamantirta, Kasihan, Bantul, Yogyakarta - Khoiruddin Khoiruddin; Kirnantoro Kirnantoro; Sutanta Sutanta (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Hands are the principal means of germs transmitting that causing diseases. Due to less of hand-washing habits, children become the highest sufferers of diarrhea and respiratory diseases, and its can end in death. Soaps have been reached to almost all of houses in Indonesia, but only about 3% that used soap every year. Approximatley the causes of died in 100,000 children in Indonesia were diarrhea, mostly in aged 5-14 years. Indonesia’s infant mortality rate was 32 per 1,000 live births. The mortality rate of nearly 19% due to diarrhea. Indonesian people’s behavior against five important time of handwashing with soap can be influenced by the level of knowledge, such a condition is evident in students SDN Ngebel Tamantirta, Kasihan, Bantul, Yogyakarta. The purpose of study was to determine the relationship between knowledge level of hand washing with soap attitudes before and after meals on student at SD N Ngebel Tamantirta, Kasihan, Bantul, Yogyakarta. This study was inferential with cross-sectional design. The respondents were all students in grade 4, 5, and 6 SDN Ngebel Tamantirta Poor Bantul Yogyakarta. Samples included 96 people. Data were taken using a questionnaire. In conclusion, there was a correlation between knowledge level of hand washing with soap attitudes before and after meals on student at SD N Ngebel Tamantirta, Kasihan, Bantul, Yogyakarta.